The Impact of Customer Relationship Management on Repurchase Decisions During the Boycott of Israeli Products: The Moderating Role of Knowledge - Sandi, Ary Kurnia; Sanjaya, Vicky F; Kurniawan, Arifa (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
Repeat purchase decisions are repeated consumer purchasing activities within a certain period of time and are positive for a product or service based on past experience, after the first purchase of a product or service. Consumers who are satisfied with the products they receive make repeat purchases. Whether Customer Relationship Management affects Purchasing Decisions and Whether Knowledge is able to moderate the relationship between the two variables. This study aims to determine how much influence Customer Relationship Management and Knowledge have in influencing repeat purchase decisions on products that are indicated to need to be boycotted. This research uses a quantitative approach. Conducted from November 2024 to April 2025. The population in this study were Generation-Z in Bandar Lampung city, totaling 149,403 people. The sampling technique used a probability sampling approach with a simple random sampling. The sample size was calculated using the Slovin method with a result of 100 respondents. The application used in analyzing data is SmartPLS4 with a structural equation model (SEM) approach. The results showed that Customer Relationship Management has a positive and significant effect on Repurchase Decision, and Knowledge cannot moderates the relationship between Customer Relationship Management and Repurchase Decision.